(untitled) (Medico Legal Update, 2021)
Acute Myeloid Leukemias (AMLs) are rare but extremely malignant neoplasms that are liable for a big amount of fatalities associated with cancer. Acute myeloid leukemia (AML) results from accumulation of abnormal myeloblasts, most commonly in the bone marrow, leading to bone marrow failure and death. The present study was carried out to evaluate MMP-2 and PG E2 in sera and of (50) AML Iraqi patients, In addition to control group involving (50) matched apparently healthy subjects. This study was done in the National center of hematology, Department of biology at AL-Mustansiyria University, Baghdad Medical City since January 2019 to June 2020. The aim of study was to determine the level of total Matrix Metalloproteinase 2 and prostaglandin E2 in patients with AML by ELISA. and study the impact of these parameters on the pathogenesis of disease, also predict the AML and how the parameters correlated with stages and severity of disease and responsiveness to therapy. Conclusion: MMP-2 decreased and elevated of PGE2 in the serum of AML patients .